Anesthetic considerations for a novel anterior surgical approach to pediatric scoliosis correction. Issue 10 (31st August 2017) - Gal, Jonathan S.; Curatolo, Christopher J.; Zerillo, Jeron; Hill, Bryan; Lonner, Baron; Cuddihy, Laury A.; Antonacci, M. D.; Betz, Randal R.; DeMaria, Samuel; Khelemsky, Yury
Summary: Background: Idiopathic scoliosis is a condition that may require surgical correction. Limitations of previous surgical modalities, however, created the need for novel methods of repair. One such technique, a newer form of anterolateral scoliosis correction, has shown considerable promise, which our center has had substantial experience performing. Aim: In this article, we present the case details of our first 105 patients for the purposes of describing the evolution and details of the anesthetic management and considerations for this procedure. Methods: A retrospective review of medical records for 105 patients undergoing anterolateral instrumentation procedure for idiopathic scoliosis correction done at a single institution from May 2014 to June 2016 was performed. The details of perioperative management as well as surgical technique were reported for all patients. Results: The mean age for patients was 14.8 years (range 10‐18); the mean weight was 49.9 kg (range 25‐82). Unilateral procedures were performed on 46.7%, with bilateral and hybrid procedures performed on 50.5% and 4.7%, respectively. The median number of levels corrected was 8 (interquartile range [IQR] 7‐9) for unilateral, right 7 (IQR 6‐7) and left 5 (IQR 4‐5) for bilateral, and 4 (IQR 4‐4.5) for hybrids. The average estimated blood loss (EBL) was 310 mL±138, with cell salvaged blood transfused in 61% of patients, and allogenic blood transfusion required in only two patients. Conclusions: The described anesthetic and analgesic management provides a framework for delivering perioperative care for this challenging procedure, which is gaining popularity as a modality for scoliosis correction.